Featured Cover. Issue 10 (9th September 2022) - Phillips, Jonathan A.; Taub, Mitchell E.; Bogdanffy, Matthew S.; Yuan, Jing; Knight, Brian; Smith, James D.; Ku, Warren W.
Abstract : The cover image is based on the Hypothesis Mode of action and human relevance assessment of male CD‐1 mouse renal adenocarcinoma associated with lifetime exposure to empagliflozin by Jonathan A. Phillips et al., https://doi.org/10.1002/jat.4329 .